The effect of job satisfaction, commitment and organizational culture on the organizational citizenship behavior of employees of the regional financial agency - Ronal Regen; Nelpera Nelka; Meri Ermadewi; Tutik Susriania (Global Econedu, 2022)
This study aims to see the effect of (1)Job satisfaction with OCB employees of the Sungai Penuh City Regional Finance Agency(2)Organizational commitment to OCB employees of the Regional Finance Agency of Sungai Penuh City(3)Organizational culture towards OCB employees of the Sungai Penuh City Regional Finance Agency(4)Job satisfaction, organizational commitment and organizational culture have a joint effect on the OCB of employees of the Sungai Penuh City Financial Agency.The population in this study is allThe employees of the Sungai Penuh City Regional Finance Agency are 37 people. And the technique of determining the number of samplestaken as respondents by using total sampling.The results of this study indicate that (1)Job satisfactionhas a positive significant effect on the OCB of employees of the Regional Finance Agency of Sungai Penuh City (2)Organizational commitmentgive a positive influence on the OCB of employees of the Regional Finance Agency of Sungai Penuh City (3)Organizational cultureprovide a positive influence on the OCB of employees of the Regional Finance Agency of Sungai Penuh City (4)Job satisfaction, organizational commitment and organizational culturejointly have a positive effect on the OCB of employees of the Regional Finance Agency of Sungai Penuh City.